BESFEST: The Preservation of Besutan Jombang Arts as Characters Building of Generation Z - Mumtaz, Rafida; Aisah, Fitria Nur; Nur Noviningtyas, Indhi (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
The negative influence of globalization in Indonesia has led to moral values decrease of generation Z. Therefore, character-based education is needed to improve the character of generation Z. One of the local arts that have high moral values is Besutan. Besutan art is a native art from Jombang which is the pioneer of Ludruk. Besutan art is an art that contains moral values that can improve generation Z. However, along with the times, Besutan art has decreased in its existence. Based on the problems that occurred, this study aims to determine the values of Besutan art in building the character of Generation Z and understand the importance of implementing BESFEST as a revitalization of Besutan art. The research method used is qualitative through literature studies from journal articles, trusted websites and interviews conducted online and offline. From the results of the literature study and interviews, it was found that generation Z experienced the decrease in moral values due to the influence of globalization. Another finding is that Besutan art has decreased in existence due to the lack of Besutan art performances in regional events and the change in art from Besutan to Ludruk. BESFEST can become a revitalization medium and become a government policy regarding Besutan arts as well as efforts to improve the character of Generation Z.